UNLOCKING OPPORTUNITY: EXAMINING THE RELATIONSHIP BETWEEN REMITTANCES AND PRIVATE SCHOOL ENROLLMENT IN NEPAL - Acharya, Bisna; Kharel, Khom Raj; Poudel, Omkar; Upadhyaya, Yadav Mani; Sigdel, Surya (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2024)
This study aims to examine the complex relationship between remittances and school enrollment. This quantitative study used descriptive and analytical research methodologies, including ARDL. This study examines the pros and cons of remittance inflows on education using empirical data and theoretical frameworks. This method considers home income, economic inequality, school availability, and long-term educational success. This model analyzes factors affecting basic private school enrollment. The negative and statistically significant coefficients (-0.269 -0.475) for lagged private enrolment show crowding-out. The private enrolment may decline after two and one-year rises. One probable explanation is increased cost competition among private schools or a shift in student preference toward government schools. LNPG and lagged LNPG (-1) coefficients are not statistically significant. This model cannot prove that population growth, whether immediate or delayed, directly affects private school enrollment. This study helps to create targeted interventions and strategies for equitable and sustainable educational advancement in Nepal.